2021
DOI: 10.1111/jcpp.13564
|View full text |Cite
|
Sign up to set email alerts
|

Pupil size and pupillary light reflex in early infancy: heritability and link to genetic liability to schizophrenia

Abstract: Background: Measures based on pupillometry, such as the pupillary light reflex (PLR) and baseline pupil size, reflect physiological responses linked to specific neural circuits that have been implicated as atypical in some psychiatric and neurodevelopmental conditions. Methods: We investigated the contribution of genetic and environmental factors to the baseline pupil size and the PLR in 510 infant twins assessed at 5 months of age (281 monozygotic and 229 dizygotic pairs), and its associations with common gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…While some twin studies on psychometric traits (i.e. IQ) suggest significant contributions from shared environment in early life 39,40 our results are in line with those from previous twin studies of eye movements and of early cognitive ability in infants 60 reporting none or marginal influence of shared environment 11,23,24,58,59 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While some twin studies on psychometric traits (i.e. IQ) suggest significant contributions from shared environment in early life 39,40 our results are in line with those from previous twin studies of eye movements and of early cognitive ability in infants 60 reporting none or marginal influence of shared environment 11,23,24,58,59 .…”
Section: Discussionsupporting
confidence: 91%
“…While unique environment effects may include different stable and temporary factors common to infant research that are not shared in a family (i.e. mood and/or measurement error linked to the eye tracker) 58,59 , the relatively high heritability speaks to the reliability of the measures studied here. In turn, contrary to our hypothesis, we found no evidence of shared environment influences in any of the measures.…”
Section: Discussionmentioning
confidence: 99%
“…In a previously study conducted in a large cohort of young Chinese twins (Guangzhou Twin Project; 309 monozygotic (MZ) and 165 dizygotic (DZ) pairs [21]) heritability was found to be approximately 60% for iris thickness and pupil diameter [22]. A study using a large cohort of twin infants (BabyTwins Study Sweden (BATSS), [23]; 510 infant twins assessed at 5 months of age; 281 monozygotic and 229 dizygotic pairs) found that baseline tonic pupil size and pupillary light re ex (PLR) were highly heritable (pupil size, 64% and constriction in response to light, 62%) and linked to genome-wide polygenic risk (PLR) scores for schizophrenia [24]. Another study on 326 female twins (mean age 64 years) from the TwinsUK Adult Twin Registry [25], reported that resting pupil size in complete darkness was strongly heritable with additive genetic effects explaining up to 86% of the variance and environmental factors explaining only 14% of the variability, and for between 31 and 60% of the variability in the PLR [26].…”
Section: Introductionmentioning
confidence: 99%